Mechanism of Interaction of Al3+ with the Proteins Composition of Photosystem II - Hasni, Imed; Yaakoubi, Hnia; Hamdani, Saber; Tajmir-Riahi, Heidar-Ali; Carpentier, Robert (PLOS ONE, 2015)
The inhibitory effect of Al3+on photosystem II (PSII) electron transport was investigated using several biophysical and biochemical techniques such as oxygen evolution, chlorophyll fluorescence induction and emission, SDS-polyacrylamide and native green gel electrophoresis, and FTIR spectroscopy. In order to understand the mechanism of its inhibitory action, we have analyzed the interaction of this toxic cation with proteins subunits of PSII submembrane fractions isolated from spinach. Our results show that Al 3+, especially above 3 mM, strongly inhibits oxygen evolution and affects the advancement of the S states of the Mn4O5Ca cluster. This inhibition was due to the release of the extrinsic polypeptides and the disorganization of the Mn4O5Ca cluster associated with the oxygen evolving complex (OEC) of PSII. This fact was accompanied by a significant decline of maximum quantum yield of PSII (Fv/Fm) together with a strong damping of the chlorophyll a fluorescence induction. The energy transfer from light harvesting antenna to reaction centers of PSII was impaired following the alteration of the light harvesting complex of photosystem II (LHCII). The latter result was revealed by the drop of chlorophyll fluorescence emission spectra at low temperature (77 K), increase of F0 and confirmed by the native green gel electrophoresis. FTIR measurements indicated that the interaction of Al 3+ with the intrinsic and extrinsic polypeptides of PSII induces major alterations of the protein secondary structure leading to conformational changes. This was reflected by a major reduction of α-helix with an increase of β-sheet and random coil structures in Al 3+-PSII complexes. These structural changes are closely related with the functional alteration of PSII activity revealed by the inhibition of the electron transport chain of PSII.